Monitoring of patients with chronic hepatitis B without liver cirrhosis while determining the tactics of treatment - O. V. Riabokon; A. B. Khelemendyk; Yu. Yu. Riabokon (Patologìâ)
Abstract Aim. The purpose of the work is to reveal the features of CHB without liver cirrhosis when assessing the need for the appointment of antiviral therapy for the implementation of the State Target Program; to compare the criteria for monitoring CHB patients without cirrhosis in existing international recommendations. Material and methods. When assessing the features of the course of CHB in 286 patients without cirrhosis, the recommendations of NICE (2013) and WHO (2015) were taken into account to determine the need for antiviral treatment, which is the basis of the clinical protocol in Ukraine. The work analyzes the international guidelines for monitoring CHB patients without cirrhosis: the American Association for the Study of the Liver Diseases (2016), the European Association for the Study of the Liver (2012), the National institute for Health and Care Excellence (2013), World Health Organization (2015).